Cardiovascular risk in patients with plaque psoriasis and psoriatic arthritis without a clinically overt cardiovascular disease: the role of endothelial progenitor cells - Michalska, Anna; Teichman, Rafał; Kręcisz, Beata; Siudak, Zbigniew; Stępień, Renata; Sadowski, Marcin (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2020)
Psoriasis is an autoimmune, chronic disease determined by environmental and genetic factors. The occurrence of psoriasis is accompanied by metabolic diseases, cardiovascular diseases (CVD) and depression, disturbances on interpersonal interactions and a tendency towards social isolation. Regardless of the form of psoriasis and the severity of the disease, early arterial lesions are recorded in arterial vessels of patients. Nevertheless, the chance of CVD is higher in the population of patients with severe psoriasis than in patients with mild to moderate psoriasis. The correlation between the presence of atherosclerotic plaque and psoriatic plaque is partially explained by: (1) a similar inflammatory pathway – via the T helper cells, (2) impaired angiogenesis, and (3) endothelial dysfunction. In the considered tests, the diagnostic tools used showed a reduced level of endothelial progenitor cells in the circulation of patients with psoriasis. Endogenous angiopoietin stimulation in patients with psoriasis leads to deterioration of endothelial regeneration, atherosclerosis which secondarily contributes to the progression of heart failure. Clinical and experimental data confirm the potential of immunomodulatory methods to combat both autoimmune and cardiovascular diseases through the use of immunosuppressive drugs. Full understanding of the way in which CVD develops in patients with autoimmune diseases would enable the implementation of targeted cell therapy allowing the quality and life expectancy of patients to be improved. Modern cellular diagnostic tools allow the use of highly specific biomarkers, which in the near future will enable a reduction in morbidity and mortality due to CVD.